The Involvement of the csy1 Gene in the Antimicrobial Resistance of Acinetobacter baumannii - Guo, Tingting; Sun, Xiaoli; Li, Mengying; Wang, Yuhang; Jiao, Hongmei; Li, Guocai (Frontiers in Medicine, 2022)
Acinetobacter baumannii is an important, opportunistic nosocomial pathogen that causes a variety of nosocomial infections, and whose drug resistance rate has increased in recent years. The CRISPR-Cas system exists in several bacteria, providing adaptive immunity to foreign nucleic acid invasion. This study explores whether CRISPR-Cas is related to drug resistance. Antibiotics were used to treat strains ATCC19606 and AB43, and the expression of CRISPR-related genes was found to be changed. The Csy proteins (Csy1–4) were previously detected to promote target recognition; however, the potential function of csy1 is still unknown. Thus, the RecAb homologous recombination system was utilized to knock out the csy1 gene from A. baumannii AB43, which carries the Type I-Fb CRISPR-Cas system, and to observe the drug resistance changes in wild-type and csy1-deleted strains. The AB43△csy1 mutant strain was found to become resistant to antibiotics, while the wild-type strain was sensitive to antibiotics. Moreover, transcriptome analysis revealed that the csy1 gene regulates genes encoding CRISPR-Cas-related proteins, drug-resistant efflux pumps, membrane proteins, and oxidative phosphorylation-related proteins, inhibiting antimicrobial resistance in A. baumannii. The in vitro resistance development assay revealed that the complete CRISPR-Cas system could inhibit the development of bacterial resistance. Our findings expand our understanding of the role of CRISPR-Cas csy1 in A. baumannii and link the CRISPR-Cas system to the biogenesis of bacterial drug-resistant structures.